IMPACT ON THE EFFECTIVENESS OF MARKETING SERVICES IN HOTELS DETERMINING FACTORS AND THEIR DETERMINATION - Usmanova Dilfuza Ilkhomovna (Research Parks Publishers, 2023)
In this article, the attraction of tourists to our country, promotion to the international level, development of hotel service, development of private entrepreneurship, improvement of the quality of service and services were considered.